Analisis Hidrologi dan Perencanaan Sistem Drainase Menggunakan GIS di Sub DAS Melangit Kecamatan Bangli - Suprianingsih, Ni Wayan; Dayanti, M A R; Prakarsa, I M P T; Kardiyasa, K A P (Jurnal Teknik Sipil Terapan (JTST), 2025)
Land use changes in the Melangit Sub-Watershed, Bangli Regency, have caused an increase in surface runoff, a decrease in infiltration capacity, and a risk of flooding in residential areas. This study aims to analyze hydrological characteristics and evaluate the capacity of the existing drainage system using a Geographic Information System (GIS) approach. The research methods included analysis of planned rainfall using the Gumbel distribution, calculation of planned discharge using the Rational method, and evaluation of channel capacity based on hydraulic parameters using the Manning equation. The results showed that the planned rainfall intensity for a 5-year return period was 177.5 mm/hour with a total runoff discharge of 40.89 m³/second. Residential areas produced the highest discharge of 11.39 m³/second, while industrial plantations produced the lowest discharge of 4.41 m³/second. Spatial analysis showed that the priority zone for drainage planning was in flat to sloping areas with high residential density. The research findings confirm that GIS-based drainage planning and conservation zoning are necessary to improve the effectiveness of runoff control and flood mitigation. In conclusion, the integration of hydrological analysis and GIS can be the basis for adaptive and sustainable drainage infrastructure planning. Keywords: Hydrological analysis, Drainage, GIS, Surface runoff, Water management system